Program PHARE 2002: technologie informatyczne jako pomoc w informatyzacji sektora małych i średnich przedsiębiorstw w Polsce - Peszko, Agnieszka (PHARE 2002 Programme: Information Technologies to Facilitate Developing Computer Applications in Small and Medium Enterprises in Poland, 2005)
Since August 2002, Polish small and medium enterprises have had an opportunity to receive grants from pre-accessive fund PHARE 2002: IT Technologies Programme for Enterprises for cofinancing development projects concerning the development of computer applications in enterprises. The article includes locations they have been granted to in the scope of the programme. There has also been drawn comparison of fund application among individual voivodeships. The attention was paid to relatively low interest of Polish businessmen from the small and medium enterprise sector in investing into information technology.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 124-131